Patterns of mortality in children presenting to a tertiary paediatric emergency unit in Sub-Saharan Africa: a cross sectional study - Josephs, Tracey (Department of Paediatrics and Child Health, 2020)
Background Pneumonia, diarrhoea and perinatal factors are the foremost killers of South African children as in other low- and middle-income countries. Poverty, poor access to care and pre-hospital care are reported major pre-hospital factors and lack of triage, poor skills, delays, poor adherence to treatment protocols and inadequate emergency care determining mortality have been reported to increase in-hospital mortality. Objectives To describe the clinical presentation and management of children admitted via the medical emergency unit (MEU) of the Red Cross War Memorial Children's Hospital (RCWMCH) who subsequently died. Methods We did a retrospective study undertaking a cross-sectional review of children who died following admission via RCWMCH MEU in 2008. Demographic information, clinical data, time factors and mortality data were reviewed and summarised by descriptive and inferential statistics. The unit utilised the WHO Emergency Triage Assessment and Treatment (ETAT) triage tool, categorising children into Red (emergency), orange (priority) and Green (non-urgent). Patient management was assessed by means of ETAT and the Integrated Management of Childhood Illness (IMCI) tools, which is used to identify severity of illness and strategize treatment plans accordingly. Results A total of 135 children met the inclusion criteria. The crude mortality rate was of 6.25 per 1000 admissions. Of the 135 children who died, 119 (88%) were under five years of age, 33(24%) were HIV-infected, of whom (88%) were under 5 years old. In 67 (50%), a chronic medical condition could be identified while 67 (50 %) were moderately or severely malnourished. There were 29 (22%) deaths within 24 hours of arrival at the MEU. Fifty-five (41%) presented after hours. Community health centres referred 65 (48%) patients, general practitioners referred 20 (15%) and 38 (28%) were self-referred. Ambulance services provided pre-hospital transport to 69 (51%). The two top presenting illnesses in 88 (65%) of the children were acute respiratory illness and acute gastroenteritis. Prior to referral, oxygen was not provided in 57 (59%) children, 35 (71%) with suspected sepsis did not receive antibiotics and glucose was not checked in 39 (80%) with depressed level of consciousness. The median time to ward transfer was 3.23 (IQR: 2.12-4.92) hours. Twelve deaths (9%) occurred in the MEU, 57 (42%) in PICU, 56 (42%) in medical wards and 10 (7%) in specialist wards. The five most common causes of death were acute respiratory infections in 45 (33%), acute gastroenteritis in 27 (20%), septicaemia 22 (16%), meningitis in 13 (10%) and cardiac conditions in 12 (9%) children. Conclusion The top causes of mortality in this hospital cohort in 2008 were pneumonia, acute gastroenteritis, and septicaemia. Using the IMCI and ETAT standard of care, suboptimal management was identified in pre-hospital management, as well as MEU management. Appropriate training and protocol implementation to improve morbidity and mortality should be undertaken.